Metaphor or ‘better-for’? An appraisal of Sallie McFague’s ‘metaphorical theology’ - Abetz, Katherine 1951- (2014)
Sallie McFague claims to base her ‘metaphorical theology’ on an amalgam of theories about metaphor. For this purpose she links C. S. Lewis’s understanding of the metaphorical origin of cognitive language with Colin Turbayne’s claim about the illusory propensity of metaphor. She also enlists Max Black’s illustration of metaphor as ‘screen’ and Paul Ricoeur’s position on the ‘is’ and ‘is not’ character of ‘metaphorical truth’. McFague’s discussion, however, omits Ricoeur’s critique of Turbayne. This article contends that McFague tends to misrepresent key theory about metaphor. It questions whether her position on metaphor is, as she asserts, similar to Ricoeur’s in terms of ontological reference and suggests a possible parallel between the position of Ricoeur and Lewis. McFague’s ‘hermeneutic of suspicion’ towards the metaphor ‘God as Father’ is argued to have a demythologizing effect on her notion of metaphor. Regarding her contention that some metaphors are better for our day, the article draws attention to a possible deconstructionist epistemology for the notion of ‘better’.
Keywords: Sallie McFague; Paul Ricoeur; Metaphor; C. S. Lewis; Colin Turbayne